2011
DOI: 10.1016/j.jns.2011.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Reduced resting potentials in dystrophic (mdx) muscle fibers are secondary to NF-κB-dependent negative modulation of ouabain sensitive Na+–K+ pump activity

Abstract: To examine potential mechanisms for the reduced resting membrane potentials (RP) of mature dystrophic (mdx) muscle fibers, the Na+ - K+ pump inhibitor ouabain was added to freshly isolated nondystrophic and mdx fibers. Ouabain produced a 71% smaller depolarization in mdx fibers than in nondystrophic fibers, increased the [Na+]i in nondystrophic fibers by 40%, but had no significant effect on the [Na+]i of mdx fibers, which was approximately double that observed in untreated nondystrophic fibers. Western blots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…Together, this suggests that the filling state of the SR contributes significantly to the dysregulation [Ca 2ϩ ] rest observed in mdx muscles. Several reports indicate that resting membrane potentials are more positive in mdx muscles fibers than WT (27,(63)(64)(65). We have found that mdx myotubes showed a partial membrane depolarization compared with WT.…”
Section: Trpc1-dependent Camentioning
confidence: 53%
“…Together, this suggests that the filling state of the SR contributes significantly to the dysregulation [Ca 2ϩ ] rest observed in mdx muscles. Several reports indicate that resting membrane potentials are more positive in mdx muscles fibers than WT (27,(63)(64)(65). We have found that mdx myotubes showed a partial membrane depolarization compared with WT.…”
Section: Trpc1-dependent Camentioning
confidence: 53%
“…Moreover, blocking this known increase in the activity of TRP channels with either a dnTRPC or a dnTRPV construct abrogated MD in mouse models of disease, suggesting that unregulated or greater activation of the TRP class of cation channels is a primary disease determinant. These channels also permeate Na ϩ , which would enhance Ca 2ϩ entry through NCX1 by favoring reverse-mode activity (7,(17)(18)(19)(20). Finally, we also previously showed that overexpression of SERCA1 in skeletal muscle, which produces higher rates of Ca 2ϩ clearance back into the SR, was protective against MD in the mouse (16).…”
Section: Discussionmentioning
confidence: 78%
“…Importantly, cytosolic Na ϩ levels appear to be elevated in myofibers from the mdx mouse, a model of Duchenne MD (7,(17)(18)(19)(20). Indeed, recent evidence suggests that intracellular Na ϩ levels are also elevated in Duchenne MD patients (21,22).…”
mentioning
confidence: 99%
“…Whilst neither agent is suitable for clinical development, treatment of the mdx mouse has demonstrated that inhibition of NF-B signalling can improve strength, reduce necrosis and enhance muscle regeneration [216,221,225]. PDTC and UDCA hyperpolarise mdx fibres by counteracting negative modulation of the resting Na + -K + pump activity and, encouragingly, PDTC had no effect in non-dystrophic mice [226]. These positive results have led to further tests in the mdx with more clinically suitable substances including curcumin, the principal curcuminoid found in turmeric and a potent NF-B inhibitor [227], and flavocoxid, a mixed flavonoid extract with anti-inflammatory, antioxidant and NF-B inhibiting properties that is marketed as Limbrel® (Primus Pharamceuticals, AZ, USA) for management of osteoarthritis [228].…”
Section: Nf-bmentioning
confidence: 99%